How to realize your scientific potential: instructions for clinicians - Л. М. Самчинська (Репродуктивная эндокринология, 2019)
While evidence-based medicine has become an indispensable condition not only in the work of doctors, but also in the priorities of patients, for many Ukrainian clinicians and researchers continue to be difficult access to the international scientific world. This article is help in the implementation of this issue.